Ipsilaterální zlomenina processus coracoideus a akromionu lopatky v kombinaci se zlomeninou laterální části klavikuly, terapeutická možnost řešení - Krtička, M; Petráš, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2019)
Superior Shoulder Suspensory Complex (SSSC) is a bone and soft-tissue ring securing the connection of the upper extremity to the axial skeleton via the clavicle and sternoclavicular joint. An isolated injury to one component of SSSC is usually stable. An injury to 2 of its components is a potential source of shoulder girdle instability and requires surgical stabilisation. An injury affecting 3 and more components is extremely rare and surgical stabilisation should be indicated. Our study presents the case of a 50-year-old man who fell off the bicycle and sustained a direct blow to his left shoulder resulting in an ipsilateral fracture of the coracoid and acromion process combined with the fracture of the distal end of the clavicle. Following a standard clinical examination and a subsequent X-ray and a CT scan with three-dimensional shoulder reconstruction, an open reduction and stabilisation of all the injured SSSC components was performed. Later, early and gradual rehabilitation of the shoulder girdle was commenced. At 48 weeks after the surgery, almost full range of motion of the shoulder joint was achieved and the muscle strength of the operated upper extremity was comparable to that of the healthy one. Key words:Superior Shoulder Suspensory Complex, fracture, acromion, coracoid process, clavicle.
Keywords: Shoulder Injuries; fraktury kostí; Scapula; Clavicle; poranění ramene; lidé; Coracoid Process; Fractures, Bone; Acromion; klíční kost; lopatka; processus coracoideus; Male; akromion; vnitřní fixace fraktury; lidé středního věku; mužské pohlaví; Middle Aged; Fracture Fixation, Internal; Humans